Inflammatory Bowel Disease Serological Immune Markers Anti-Saccharomyces cerevisiae Mannan Antibodies and Outer Membrane Porin C are Potential Biomarkers for Hirschsprung-associated Enterocolitis. Issue 2 (August 2019) - Frykman, Philip K.; Patel, Deven C.; Kim, Sungjin; Cheng, Zhi; Wester, Tomas; Nordenskjöld, Agneta; Kawaguchi, Akemi; Hui, Thomas T.; Ehrlich, Peter F.; Granström, Anna L.; Benliyan, Filip
ABSTRACT: Objective: Hirschsprung-associated enterocolitis (HAEC) is the most frequent complication in Hirschsprung disease (HSCR) patients. Currently HAEC is diagnosed clinically, leaving uncertainty in the diagnosis thereby potentially leading to over- or undertreatment of patients. The aim of this study was to identify immune biomarkers to aid in the diagnosis of HAEC. Methods: From 2012 to 2017, 43 children with HSCR enrolled in a multicenter study, underwent retrospective evaluation of their medical records, and questionnaire-directed parent interviews. HAEC status was determined using HAEC score with cutoff ≥4. Plasma was collected and analyzed by ELISA for the inflammatory bowel disease–associated antibodies: anti- Saccharomyces cerevisiae mannan antibodies (ASCA), outer membrane porin C (OmpC), CBir1, antineutrophil cytoplasmic antibodies. Data were analyzed using t test, univariate, multivariable, and binomial regression models. Results: Eighteen patients had at least 1 episode of HAEC, 25 had no history of HAEC. The HAEC and NO HAEC groups had similar median ages (3 years) and family histories of HSCR. The HAEC group showed markedly elevated ASCA IgA and OmpC antibody levels compared with the NO HAEC group, whereas CBir1 and antineutrophil cytoplasmic antibodies were similar between the groups. Both univariate and multivariable analysis revealed higher OmpC antibody levels associated with HAEC (odds ratio 1.39, confidence interval 1–1.92, P  = 0.048), whereas univariate analysis identified a trend toward elevated IgA and immunoglobulin G ASCA levels with HAEC. Conclusions: We identified elevated OmpC and ASCA serum antibody levels in HAEC patients, and that increased OmpC antibody levels correlated with HAEC occurrence, suggesting HAEC and Crohn disease share gut microbial-host immune responses. These antibodies may serve as potential biomarkers for HAEC, although prospective study with larger sample size is needed.